Characteristics of Upper Limb Impairment Related to Degenerative Cervical Myelopathy: Development of a Sensitive Hand Assessment (Graded Redefined Assessment of Strength, Sensibility, and Prehension Version Myelopathy). Issue 3 (3rd December 2019) - Kalsi-Ryan, Sukhvinder; Riehm, Lauren E; Tetreault, Lindsay; Martin, Allan R; Teoderascu, Florentina; Massicotte, Eric; Curt, Armin; Verrier, Mary C; Velstra, Inge-Marie; Fehlings, Michael G
Abstract: BACKGROUND: Degenerative cervical myelopathy (DCM) involves spinal cord compression, which causes neurological decline. Neurological impairment in DCM is variable and can involve complex upper limb dysfunction including loss of manual dexterity, hyperreflexia, focal weakness, and sensory impairment. The modified Japanese Orthopaedic Association (mJOA) score relies on the patients' subjective perceptions, whereas existing objective measures such as strength and sensory testing do not capture subtle changes in dexterity and function. OBJECTIVE: 1) To characterize arm and hand function in DCM; and 2) To develop and validate Graded Redefined Assessment of Strength, Sensibility, and Prehension Version-Myelopathy (GRASSP-M), a clinical assessment that quantifies upper limb impairment. METHODS: A total of 148 DCM patients (categorized into mild, moderate, and severe based on mJOA grade) and 21 healthy subjects were enrolled. A complete neurological exam, the mJOA, the QuickDASH, grip dynamometry, and the GRASSP-M were administered. RESULTS: Strength, sensation, and manual dexterity significantly declined with increasing DCM severity ( P  ≤ .05). Impairment in hand dexterity showed better discrimination between mild, moderate, and severe DCM categories than strength or sensation. The GRASSP-M was found to be both a reliable (intraclass correlation coefficient >0.75 for intra- and inter-rater reliability) and valid (with both concurrent and construct validity) tool. CONCLUSION: These results demonstrate that patients' subjective reporting of functional status, especially in the mild DCM category, may underrepresent the extent of functional impairment. The GRASSP-M is an objective tool designed to characterize patients' functional impairment related to the upper limb, which proves useful to diagnose and quantify mild dysfunction, monitor patients for deterioration, and help determine when patients should be treated surgically.